Contribución de las estrategias de promoción en la fidelización de clientes de las empresas exportadoras de café especial peruano en Estados Unidos: periodo 2015 – 2020 - Sugashima Brocca, Alfredo Jose Akira (2022)
This thesis entitled "Contribution of Promotion Strategies on Customer Loyalty of Peruvian Specialty Coffee Exporting Companies in the United States: 2015-2020 Period", had as its main objective to analyze the contribution of promotion strategies on customer loyalty. clients of Peruvian specialty coffee exporting companies to the United States: period 2015 - 2020. Therefore, it is exploratory research with qualitative design. The population and sample were defined by experts and specialists in the Peruvian coffee export area and state entities (PROMPERU, Ministry of Agrarian Development and Irrigation, SENASA). The data collection techniques were the survey and the interview, while the data collection instruments were the questionnaire and the interview guide. Similarly, among the conclusions, it is highlighted that the level of efficiency for the 2015-2020 period was high, basically because the promotion strategies used were hybrid (push and pull). The level of loyalty is high, basically because it allowed to achieve an increase in the level of sales and the trust of customers in a quality product. In addition, international customer confidence and the scope of higher sales were achieved. Customers are motivated by testing a sample, seeing that they are different and good. A history of large buyers prevails, there are contracts of 3, 4 and 5 years onwards with cooperatives in the perception of this raw material.